PERPUSTAKAAN UMUM KECAMATAN LANDASAN ULIN - Herlina Septiani Herman; Indah Mutia (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Libraries play an important role as centers of literacy, education, and social interaction. However, in Banjarbaru City, particularly in the Landasan Ulin District, the availability of adequate literacy facilities remains limited in terms of spatial distribution, capacity, and the ability of spaces to respond to diverse learning patterns and literacy activities of students and university learners. This study aims to design an Adaptive Public Library in Landasan Ulin by applying a programming method to comprehensively analyze user needs, site conditions, and building functions. The adaptive concept is implemented to address evolving learning behaviors and dynamic literacy activities through spatial flexibility, legible circulation systems, and the integration of digital technology as support for user activities. This approach allows the library to function not only as a reading facility but also as a community-oriented public space capable of accommodating future changes in user needs. The design outcome is expected to provide a relevant, comfortable, and responsive literacy facility that supports the development of learning culture in the Landasan Ulin District.